Bis{μ-2,5-bis[4-(2-pyridylmethylamino)phenyl]-1,3,4-oxadiazole}bis[dichloridomercury(II)] - Liu, Li-Li (International Union of Crystallography, 2008)
In the title centrosymmetric compound, [Hg(2)Cl(4)(C(26)H(22)N(6)O)(2)], each Hg(II) center adopts a distorted HgN(3)Cl(2) trigonal bipyramidal coordination geometry, formed by two pyridine N atoms, one imine N atom and two chloride anions. Within the organic ligand, the oxadiazole ring is nearly coplanar with the two benzene rings [dihedral angles = 5.9 (4) and 6.5 (4)°] and nearly perpendicular to the two pyridine rings with the same dihedral angle of 77.4 (4)°. The two organic ligands bridge two Hg(II) ions to form the macrocyclic complex. Intermolecular N—H⋯Cl and N—H⋯N hydrogen bonding helps to stabilize the crystal structure.